HOW ATTITUDINAL AND BEHAVIOURAL LOYALTY IS FORMED? A CASE OF GARUDA INDONESIA’S CUSTOMER SATISFACTION - Kunthi A. Kusumawardani; Veronica Elsya; Suresh Kumar (FIRM Journal of Management Studies, 2017)
The purpose of this research is to examine service quality and perceived price fairness in airline industry and how these variables influences customer satisfaction and attitudinal and behavioural loyalty. The research is based on the sample of 304 Garuda Indonesia’s customers who have completed 37 questions questionnaire. This research uses Structural Equation Modelling (SEM) to analyse the responses. The research concludes that tangibility, assurance, and empathy are factors in service quality that significantly influence customer satisfaction. Furthermore, customer satisfaction and perceived price fairness also influence attitudinal and behavioural loyalty. This research is limited on the evaluation of Garuda Indonesia airlines among Indonesian passengers. Thus, this research cannot be generalised to the other airline passengers, in Indonesia or other countries. This research provides the first insight of Indonesian national airline, Garuda Indonesia, especially in the terms and relationship of perceived price fairness, customer satisfaction, and attitudinal and behavioural loyalty.